The Carbon Effect in Biodiesel Synthesis - Setiawan, Mohammad Arfi; Morentera, Brilian Gema (Al-Kimia, 2020)
Biodiesel is synthesized from the trans-esterification reaction of vegetable oil and alcohol using a catalyst such as acids, bases or enzymes. The acid catalyst that is often used is sulfuric acid; H2SO4, and HCl while most of base catalysts are NaOH and KOH. The aim of this study is to determine the effect of carbon derived from sugar heating in the synthesis of biodiesel with a sulfuric acid catalyst; H2SO4. Trans-esterification reaction of Jatropha oil and methanol with sulfuric acid catalyst was done with oil and methanol at 1:9 ratio. The results showed that (1) the physical properties of the biodiesel was synthesized with carbon-H2SO4 has a difference with physical properties the biodiesel was synthesized by sulfuric acid (2) carbon-H2SO4 was used in the trans-esterification reaction of Jatropha oil and methanol to produce methyl ester character is the density of 0.889 g / mL, 24.59 cSt viscosity and refractive index of 1.464, (3) methyl ester produced from the reaction of trans-esterification of Jatropha oil and methanol with sulfuric acid catalyst has a character that is a density of 0.882 g / mL, 11.70 cSt viscosity and refractive index of 1.458.